Design of a smart LED lighting system for sleeping hours - Ting, Leonard Heng Zhou (2017)
Smart lighting is a lighting technology designed to provide people with the convenience of having automated controls based on different types of conditions. With the advancement of technology, engineers are able to come out with many different types of ideas to design, implement and upgrade the existing lighting technologies. The intent of this project is to design and develop a Smart LED Lighting System for operation during sleeping hours. In this report the development of a Smart LED Lighting System will be documented. This lighting system aims to achieve the purpose of being able to detect the different sleeping status of a person during their sleep to ON/OFF or dim the light source. This is done by using a motion sensor to detect the duration of the body movement of the person to control the light source. This system will be able to provide automatic and flexible control needed during the night to navigate through the room when it is dark. All in all, the aim of this project is to design and construct a prototype model to demonstrate the concept of the Smart LED Lighting System for the operation during sleeping hours.